Karakteristik Pendidikan Jesuit dalam Pendidikan Dasar dan Menengah di Perkumpulan Strada - Witono, Odemus Bei; Maridjo, H. Herry (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2021)
Strada Association is an educational community belonging to the Archdiocese of Jakarta which was founded by three Jesuits. The establishment and management of the Strada Association has until now been entrusted to the Society of Jesus. Strada’s long history indicates that there are characteristics of Jesuit education to be found there. However, since its inception, the characteristics of Jesuit education have not been clearly revealed in the manual on how to act for teachers and leadership elements within the Strada Association. The purpose of this research is to find out the important elements, and the ways in which Branch Head, Supervisor, Principals, and teachers to experience fully, live, and implement the characteristics of Jesuit education in the Strada Association. Through qualitative research methods, researcher seeks to find the characteristics of Jesuit education through in-depth interviews, with key persons (informants), namely people who the author believes know about the situation of the Strada Association. Data analysis was carried out by observing the appreciation, livelihood, and implementation of the characteristics of Jesuit education. The results of the study indicate that the characteristics of Jesuit education in general have been, and are being lived, lived, and implemented by the interviewed informants. The conclusion that can be drawn is that the characteristics of Jesuit education can be found in the Strada Association community.